Arsenic and Trace Metal Concentrations in Tissues of Two Economically Important Fish Species (Chrysichthys nigrodigitatus and Sarotherodon melanotheron) from Western Ebrie Lagoon, Côte d’Ivoire - Ayénan Marc-Olivier Togbé; Koffi Marcellin Yao; Kakou Charles Kinimo; Kouamé Victor Kouamé; Boua Celestin Atsé; Abiba Sanogo Tidou (Earthline Journal of Chemical Sciences, 2023)
Total concentrations of trace metals Hg, Cd, and Pb, and metalloid As were measured monthly (December 2014 to November 2015) in two fish species, Chrysichthys nigrodigitatus and Sarotherodon melanotheron at five sites in the western part of the Ebrie Lagoon (Côte d’Ivoire). Results indicated that Chrysichthys nigrodigitatus muscle accumulated significant amount of total Hg, Cd, and As than Sarotherodon melanotheron, while no significant difference was found for Pb. Average total Hg and As concentrations showed opposite spatial trends, while Pb and Cd registered no spatial variation in Chrysichthys nigrodigitatus. On contrary, insignificant seasonal variation was observed for average total Hg, Cd, Pb, and As concentrations in Sarotherodon melanotheron. In overall, Cd and Pb concentrations in fish exceeded the safety limits set by the European Commission in 10 to 40% of the total individuals, but the maximum safe weekly consumption values of fish estimated were very high and unlikely to be reached by local communities.